Angiomatoid fibrous histiocytoma: clinicopathological and molecular characterisation with emphasis on variant histomorphology. Issue 3 (16th September 2013) - Kao, Yu-Chien; Lan, Jui; Tai, Hui-Chun; Li, Chien-Feng; Liu, Kai-Wen; Tsai, Jen-Wei; Fang, Fu-Min; Yu, Shih-Chen; Huang, Hsuan-Ying
Abstract : Aims: Angiomatoid fibrous histiocytoma (AFH) is histologically typified by nodules of histiocytoid spindle cells with pseudoangiomatoid spaces, fibrous pseudocapsules and lymphocytic cuffs. The principal goal was to expand the spectrum of AFHs through clinicopathological and molecular characterisation. Methods: Thirteen AFHs, including 11 with confirmed hallmark translocation, were reappraised for classic features, reactive osteoclasts, mitoses and stromal, architectural and cytomorphological variations, with CD99, desmin and EMA stained in available cases. Results: Seven male and six female patients ranged in age from 4 to 63 years (median, 13), including 4 older than 20 years. Tumours were located on the extremities (n=6), trunk (n=4) and scalp (n=3). Although fibrous pseudocapsules were observed in all cases, four showed solid histology without pseudoangiomatoid spaces and another one lacked peripheral lymphoid infiltrates. Nuclear pleomorphism was striking in two cases, moderate in seven and absent in four, with osteoclasts seen in two cases. In three AFHs with sclerotic matrix, one exhibited perivascular hyalinisation and nuclear palisading, reminiscent of a schwannoma. In three varyingly myxoid tumours, one closely resembled a myoepithelioma with prominent reticular arrangement of spindle cells in an abundant myxoid stroma. Besides EWSR1 gene rearrangement detected in four cases by fluorescence in situ hybridisation (FISH), EWSR1-CREB1 fusion was confirmed in nine cases, including a schwannoma-like AFH, and EWSR1-ATF1 fusion detected in a myoepithelioma-like AFH. Immunohistochemically, 56% of AFHs were positive for EMA, 78% for desmin and 100% for CD99. Conclusions: Molecular testing is diagnostic of variant AFHs displaying diverse histomorphological alterations in the architectural patterns, cytomorphology and extracellular matrix.